التنمية الزراعية في السودان : الواقع ، التحديات ، الفرص - عبدالله، عبدالله أحمد (الهيئة العربية للاستثمار والانماء الزراعي, 2006)
الزراعة بمفهوم التنمية الزراعية المستدامة تعني إدارة وصيانة القاعدة الموردية الزراعية وحمايتها من التدهور بهدف ضمان تحقيق حاجات البشر الغذائية للأجيال الحاضرة ولتلك المقبلة وفق نمط قطاعي متوازن يجمع البنية الاجتماعية والاقتصادية والبيئية. وتشير الدراسة الحالية إلى السعة أو الموقع الجغرافي المتميز للسودان ومناخه وتقسيماته الأيكولوجية المتعددة التي تؤهله لزراعة العديد من المحصولات وتربية الماشية وحتمية تكامل القطاع بشقيه النباتي والحيواني. وإلى القاعدة الموردية الزراعية الهائلة التي تشمل الأراضي الزراعية والمياه والموارد الوراثية والغابات والمراعي والأسماك والحياة البرية. وهي موارد أهلت السودان ليكون أحد ثلاث بلاد مرشحة للمساهمة في توفير الغذاء في العالم. كما تستعرض النظم الزراعية التي انبثقت من الظروف المناخية والبيئات الزراعية والموارد المتاحة، ونظم استخدام الموارد الزراعية. ولكل من هذه النظم سماته وميزاته وخصائصه ومنافعه ومخاطره وتحدياته وسبل تطوير. يمثل القطاع الزراعي الإنتاج الرئيسي المستدام والقوة الرئيسية المحركة للاقتصاد الوطني لكون السودان يتميز بموارده الزراعية الهائلة التي يستغل منها حالياً حوالي 20% من الأراضي الصالحة وثلثي نصيبه من الماء. كما يزخر السودان بمراعي طبيعية واسعة تقوم عليها ثروة حيوانية هائلة إضافة إلى الغابات والمخزون السمكي. ويتميز السودان كذلك ببيئات زراعية متعددة تتيح زراعة العديد من المحاصيل النقدية والغذائية والصناعية تشمل القطن وقصب السكر والذرة الرفيعة والقمح والبقوليات والبذور الزيتية إضافة إلى الصمغ العربي. كما تستعرض الدراسة التحديات الرئيسية التي تواجه التنمية الزراعية أهمها ضعف الإنفاق العام على الزراعة والبني التحتية المساندة لها والإنتاجية الزراعية المنخفضة كما ونوعا وقاعدة إنتاج متواضعة وتذبذب في الإنتاج وتكلفة عالية وظاهرة الجفاف وضعف هيكلة القطاع الزراعي وضمور الاستثمار الزراعي. وحتى تمضي النفرة الخضراء إلى مقاصدها يتوجب وضع استراتيجية زراعية واضحة الرؤوس والأهداف والقدرات البشرية والمتابعة والتقويم، واستعرضت الدراسة الأهداف والسياسات الكلية والقطاعية المطلوبة للنهضة الزراعية مع مراعاة أهم التغيرات العالمية ذات الأثر على الزراعة وسبل تمكين القطاع من مواجهة العولمة.. "إن صلاح أهل السودان يقع في صلاح زراعتهم" بالرغم من الاكتشاف الجديد للبترول. Sustainable agricultural development implies management of the natural agricultural resource base to satisfy the food needs of the present generation and conservation of those resources against degradation to ensure the needs of future generations, in accordance with a balanced pattern of social, economic and environmental factors. The present study highlights the capacity and distinguished geographical location of the Sudan, its climate and the various ecological zones that qualify it for the cultivations of various crops as well as animal production in an inevitable integrated plant and animal system, utilizing the enormous agricultural resource base including land, water, genetic resources, forests, range, fishery, and wildlife. These resources qualified the Sudan to be one of three countries that can contribute addressing the world food problem. The study also reviews the agricultural systems which have evolved from the climate conditions, agricultural environments, and available resources and their usage. Each of there systems has its own features, characteristics, merits, risks, challenges and means of development. The agricultural sector represents the main sustainable production and the major driving force for the national economy, as the Sudan is characterized by enormous agricultural resources, of which only about 20% of the cultivable land and two-thirds of its share of the Nile water are presently utilized. The Sudan is also rich with natural pastures supporting a huge animal wealth, in addition to the forests and fish reserve. The Sudan is also characterized by various agricultural environments allowing the cultivation of different cash, food, and industrial crops which include cotton, sugar cane, sorghum, wheat, pulses, oil seeds and gum arabic. The study also reviews the major challenges facing agricultural development, mainly: limited public spending on agriculture and infrastructure supporting it, low productivity and quality, modest production base, fluctuation of production, high cost of production, drought, weakness of the structure of the sector, and poor investment opportunities. In order for the declared green mobilization to succeed there is need for a strategy with clear objectives, human resources, follow-up, assessment and corrective measures. The study made a slight reviews of the objectives, macro and microeconomic and sectorial policies required for revival, taking into consideration the most important global changes which have an impact on agriculture and ways that enable the sector to face globalization. The future welfare of the Sudanese people is in agricultural reform, despite the newly discovered oil .
Keywords: الإنتاج الزراعي -- التنمية الزراعية -- السياسة الزراعية -- استصلاح الأراضي -- التنمية المستدامة -- الاقتصاد الزراعي -- زيادة الإنتاج -- التكنولوجيا الزراعية -- الموارد الزراعية -- الأراضي الزراعية -- مياه الري -- الأمن الغذائي -- الانتاج الغذائي -- إنتاج الحبوب -- السودان -- البنى التحتية